(untitled) (Praxis Educativa, 2014)
This paper tries to respond to the invitation from the III Conference of Life Histories in Education, to think about knowledge in biographical educational research. In addition, on the role of knowledge in social research. With this purpose, I will explore other ways to approach the meaning of knowing. All in dialogue with our biographical research experience on how young teachers learn to be a teacher in a post-capitalist working context. This reflection leaves to conclude that, when generating knowledge from a biographical and, generally, a narrative research, we do not use an inferential, hypothetical-deductive position based on a propositional rationality. Instead, and without departing from the rigor that provides reflectivity, the knowledge generated is experiential, relational, narrative, reflective, educational and networking.